Application of biochar for soil erosion control and environmental management: implications for achieving sustainable development goals - Prabhakar Sharma; Shakir Ali; Jayanta Kumar Biswas (Discover Soil)
Abstract Soil erosion poses a significant threat to sustainable land management and environmental stability. This requires effective strategies for soil conservation. Biochar, a carbon-rich substance obtained from the pyrolysis of organic matter has emerged as a sustainable solution for soil erosion in the framework of United Nation’s sustainable development goals (SDGs). However, there is a lack of knowledge in understanding the diverse applications of biochar in combating soil erosion across various soil types and environmental contexts. This study comprehensively analyses the existing literature to elucidate the multifaceted benefits of biochar, such as soil structure improvement, soil nutrient retention enhancement, and intensity of soil microbial activity. This study highlights the importance of biochar applications in sustainable development practices and emphasizes biochar’s potential contributions in achieving SDGs, particularly those related to environmental conservation and land management. By synthesizing current research findings and case studies, the study reveals that there is a need to stress biochar uses as a feasible and eco-friendly tool in addressing soil erosion challenges due to water and advancing global sustainability. The study provides insights into future research directions and policy implications for effectively integrating biochar into holistic soil management strategies. This may likely pave the way for enhanced global environmental resilience and sustainable development.